IFN-I Mediates Lupus Nephritis From the Beginning to Renal Fibrosis - Ding, Xuewei; Ren, Yi; He, Xiaojie (Frontiers in Immunology, 2021)
Lupus nephritis (LN) is a common complication of systemic lupus erythematosus (SLE) and a major risk factor for morbidity and mortality. The abundant cell-free nucleic (DNA/RNA) in SLE patients, especially dsDNA, is a key substance in the pathogenesis of SLE and LN. The deposition of DNA/RNA-immune complexes (DNA/RNA-ICs) in the glomerulus causes a series of inflammatory reactions that lead to resident renal cell disturbance and eventually renal fibrosis. Cell-free DNA/RNA is the most effective inducer of type I interferons (IFN-I). Resident renal cells (rather than infiltrating immune cells) are the main source of IFN-I in the kidney. IFN-I in turn damages resident renal cells. Not only are resident renal cells victims, but also participants in this immunity war. However, the mechanism for generation of IFN-I in resident renal cells and the pathological mechanism of IFN-I promoting renal fibrosis have not been fully elucidated. This paper reviews the latest epidemiology of LN and its development process, discusses the mechanism for generation of IFN-I in resident renal cells and the role of IFN-I in the pathogenesis of LN, and may open a new perspective for the treatment of LN.